Analysis of the recombination event generating a vesicular stomatitis virus deletion defective interfering particle. - Yang, F (1983)
cDNA clones of different portions of the L cistron and 5'-terminal region of the vesicular stomatitis virus genome have been prepared and used to identify the exact site of the deletion in the defective interfering particle, DI-LT. The deletion extends from nucleotide 251 from the beginning of the L gene to a position 342 nucleotides from the end of the genome. The nucleotide sequences flanking the deletion site, as well as those at the ends of the deleted segment, did not contain any obvious vesicular stomatitis virus initiation or termination signals as had been found near the recombination sites in other defective interfering particle RNAs. The results best fit a model for the origin of this type of defective interfering particle in which the polymerase interrupts its synthesis and moves with its nascent daughter strand to a new position on the template and resumes synthesis there, further extending the nascent strand. Neither the interruption nor the resumption of synthesis appears to be in response to the template nucleotide sequence. The sequences of two partial L cistron clones also reveal open reading frames that code for amino acid sequences likely to be the amino and carboxy termini of the L protein.